The Characteristics and Functions of Bayan Accordion in Chinese Folk Music - Yanan, Li; Pattananon, Nicha (Journal of Roi Kaensarn Academi, 2024)
The Bayan accordion originated in Europe and subsequently became known around the world as a result of cultural exchanges and population movements. Given that the invention, construction and cultural formation of the accordion occurred in Europe, it is evident that the instrument has a strong European background. Over the course of a century, the accordion has evolved into one of the most popular instruments in China, particularly in the context of China's reform and opening up. The accordion has a wide range of audience groups in China. The modern accordion has overcome many of the shortcomings of the traditional accordion, including the body of the instrument, a single style, the model specifications, and so on. Currently, in China, the accordion is popular because The accordion's multifaceted appeal, encompassing its vibrant appearance, an array of models catering to diverse preferences, its rich tonality, expressiveness, portability, and the ability to emulate an entire orchestra, has cemented its status as a prevalent musical instrument. China has witnessed the flourishing of a plethora of accordion styles, including the keyboard accordion, bayan accordion, keyboard free bass accordion, and bayan free bass accordion. This article presented the characteristics and functions of Bayan accordion in Chinese folk music.